Study of Compliance of Sealed Bottled Water with Nepal Drinking Water Quality Standard: A Case of Bhaktapur Municipality, Nepal - Raj Neupane, Prasidha; Bajracharya, Iswor; Prajapati, Meera; Sujakhu, Hishila; Awal, Pramod (International Journal of Environment, 2019)
Bottled water is generally considered safe for drinking. However, several studies have reported the substandard quality of bottled water. Physico-chemical assessment of ten different brands of bottled water distributed in Bhaktapur Municipality was carried out from January 2018 to March 2018. In total, one hundred bottled water samples consisting of ten different brands were collected randomly from various retail outlets. Eight selected physico-chemical and microbiological parameters were analysed following standard methods, and the results were compared with the Nepal Drinking Water Quality Standard (NDWQS) (2005). Out of one hundred samples, sixty-nine samples did not comply with the standard pH limit. Other physico-chemical parameters were found to comply with the standard though variations were observed in the concentrations among different brands. Microbial contamination was not found in any brands of the bottled water samples considered in this study. However, it is necessary to examine other contaminants such as heavy metals, minerals, and chemicals to know the overall quality of water. Moreover, the regulatory bodies are required to strictly monitor water processing companies for the maintenance of the quality of bottled water.